2013
DOI: 10.1161/atvbaha.113.301309
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Heparanase Regulates Heart Metabolism by Stimulating Lipoprotein Lipase Secretion From Cardiomyocytes

Abstract: A fter diabetes mellitus, the heart has an increased reliance on fatty acids (FAs) for generation of energy.1 The majority of these FAs come from breakdown of circulating triglyceride-rich lipoproteins, a process catalyzed by lipoprotein lipase (LPL) located at the luminal side of vascular endothelial cells (ECs).2-4 ECs do not express LPL. In the heart, LPL is synthesized in cardiomyocytes and secreted to ECs. 5 We have previously reported an increase of coronary LPL in animal models of type 1 diabetes melli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…As we previously reported (18), glucose stimulated secretion of the latent and active forms of heparanase from EC (Fig. 7A).…”
Section: Increased Coronary Lpl Activity After Diabetes Is Related Tosupporting
confidence: 86%
See 2 more Smart Citations
“…As we previously reported (18), glucose stimulated secretion of the latent and active forms of heparanase from EC (Fig. 7A).…”
Section: Increased Coronary Lpl Activity After Diabetes Is Related Tosupporting
confidence: 86%
“…In CHO cells, latent heparanase triggers clustering of both syndecan-1 and -4, followed by rapid internalization of the heparanase-HSPG complex (31). Because we have previously reported clustering of syndecan-4 when cardiomyocytes are exposed to latent heparanase (18), it is possible that such a heparanase-HSPG complex is also responsible for endocytosis of this enzyme in cardiomyocytes. Nevertheless, we cannot rule out the contributive effects of other receptors, such as LDL receptor-related proteins and mannose 6-phosphate receptors, in this heparanase-uptake process (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14] More recently, we established a novel role for Hep A in modulating cardiac metabolism during diabetes. 10,15 The above studies in cancer and diabetes fixated on the effects of Hep A , incorrectly assuming that only the HSPG-hydrolyzing ability of heparanase was of importance. Intriguingly, Hep L also has some remarkable properties, including its ability to activate signalling elements like Erk1/2, PI3K-AKT, RhoA, and Src, which in turn can contribute to changes in transcription.…”
Section: In Cancer Biology Hepmentioning
confidence: 99%
“…Wang et al (11) previously showed that the active form of heparanase, derived from the endothelial cells, helps in cleaving and releasing LPL from the heparin sulfate proteoglycans on cardiomyocyte cell surface, whereas the inactive form serves in bringing the intracellular LPL pool to the membrane surface following RhoA activation. Active heparanase also was found to release vascular endothelial growth factor (VEGF) from the same proteoglycan holder (12).…”
mentioning
confidence: 99%